Spanish Women Making Risky Decisions in the Social Domain: The Mediating Role of Femininity and Fear of Negative Evaluation - Villanueva-Moya, Laura; Expósito, Francisca (Frontiers in Psychology, 2020)
Authors have empirically evidenced that cultural stereotypes influence gender-typed behavior. With the present work, we have added to this literature by demonstrating that gender roles can explain sex differences in risk-taking, a stereotypically masculine domain. Our aim was to replicate previous findings and to analyze what variables affect women making risky decisions in the social domain. A sample composed of 417 Spanish participants (281 women and 136 men), between 17 and 30 years old (M = 22.34, SD = 3.01), answered a set of self-report measures referring to femininity, fear of negative evaluation, and social risk-taking. According to the main results, sex indirectly linked to risk-taking in the social domain, through femininity and fear of negative evaluation. Specifically, women (versus men) self-reported higher feminine traits, which were associated with increased fear of negative evaluation, which, in turn, was associated with less risky decisions in the social domain. Thus, we have showed the relationship between gender roles and women’s behaviors in a stereotypically masculine domain (risk-taking). Our findings highlight the necessity of considering a gender-based perspective in the field of risk-taking, showing that not all women make more risky decisions in the social domain.